Can single molecule localization microscopy detect nanoclusters in T cells?. (August 2019) - Feher, Kristen; Halstead, James M; Goyette, Jesse; Gaus, Katharina
Abstract : Nanoclusters of cell surface receptors have been detected with single molecule localization microscopy (SMLM) and are thought to mediate signal transduction. Clustering of the T cell receptor (TCR), for example, was reported to control signalling efficiency and antigen discrimination. However, the ability to detect nanoclusters with SMLM has been questioned. Here, we review the detection limits of SMLM as defined by both the physical limits and data processing, as well as evidence for nanoclusters arising from complementary techniques. We conclude with an outlook of how future data analysis can reveal the implications of molecular self-organization for signalling.